Evaluation of Quantitative, Qualitative Traits and Compatibility of Rice Genotypes in Two Regions of Iran - Nasim Ranjkesh (Polish Journal of Natural Sciences, 2023)
xperiment was conducted with 30 rice genotypes in a randomized complete block design with four replications in two regions of Mazandaran Province (Amol and Sari) in 2018–2019. The results of composite variance analysis of data showed that the interaction between genotype and location on all quantitative and qualitative traits was significant except for grain yield. A significant difference was found between the studied genotypes in terms of grain yield, indicating genetic diversity of the studied genotypes. The results showed that Amol II, Dasht and Keshvari cultivars had acceptable grain yield and desirable quality characteristics. The grain yield had a positive and direct correlation with traits of the plant height, panicle length, number of fertile tillers per hill and Thousand grain weight, but this correlation was not significant.